2011
DOI: 10.1039/c0pp00259c
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for unresectable cholangiocarcinoma: contribution of single operator cholangioscopy for targeted treatment

Abstract: Photodynamic therapy (PDT) for unresectable cholangiocarcinoma is associated with improvement in cholestasis and survival. Single operator cholangioscopy (SOC) has been used for targeted laser illumination. We analyzed our growing experience of SOC with direct PDT. This is a retrospective analysis of a consecutive series of patients prospectively entered into a registry. Forty-five patients (24 male, aged 67.3 ± 10.6 years) were treated with PDT for cholangiocarcinoma during a five-year period. Thirty-two pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…It also has been shown to influence decisions regarding patient management 5,6. Our group compared PDT versus SOC directed PDT and found the therapies to be comparable without an increase in adverse complications, but with decreased radiation exposure in the SOC-directed group 15. Another recent study demonstrated that direct POC-guided PDT using an ultraslim upper endoscope is both feasible and safe in select patients with inoperable extrahepatic cholangiocarcinoma 16…”
Section: Discussionmentioning
confidence: 80%
“…It also has been shown to influence decisions regarding patient management 5,6. Our group compared PDT versus SOC directed PDT and found the therapies to be comparable without an increase in adverse complications, but with decreased radiation exposure in the SOC-directed group 15. Another recent study demonstrated that direct POC-guided PDT using an ultraslim upper endoscope is both feasible and safe in select patients with inoperable extrahepatic cholangiocarcinoma 16…”
Section: Discussionmentioning
confidence: 80%
“…Cholangioscopy-guided PDT allows for the identification of tumor margins and determination of the appropriate location for placement of the diffuser (Figure 4); it also allows for evaluation of the response to therapy (Figure 5). Talreja et al compared patients undergoing PDT with those undergoing cholangioscopy with direct PDT [69]. While the median survival time between the groups was not different, there was a statistically significant difference between the groups in terms of fluoroscopy time, as median time was 21.1 min with PDT and 11.1 min with cholangioscopy with direct PDT, thus allowing for decreased radiation exposure for both patients and healthcare professionals.…”
Section: Locoregional Therapies Photodynamic Therapymentioning
confidence: 91%
“…In a study, the median survival of patients treated with PDT only was 200 days compared with 386 days in those treated with cholangioscopy with direct PDT (P 5 .45). 18 Cholangioscopy permitted targeted therapy during PDT while simultaneously reducing exposure to radiation (21.1 vs 11.1 minutes, P<.0001). 18 In a small prospective study, PDT under direct peroral cholangioscopy with an ultraslim upper endoscope was successfully performed in 7 of 9 patients and in 15 of 17 sessions.…”
Section: Current Controversy/future Considerationsmentioning
confidence: 95%
“…18 Cholangioscopy permitted targeted therapy during PDT while simultaneously reducing exposure to radiation (21.1 vs 11.1 minutes, P<.0001). 18 In a small prospective study, PDT under direct peroral cholangioscopy with an ultraslim upper endoscope was successfully performed in 7 of 9 patients and in 15 of 17 sessions. 19 Biliary drainage under direct peroral cholangioscopy was possible in 7 of 7 patients who needed it after PDT.…”
Section: Current Controversy/future Considerationsmentioning
confidence: 95%